BOARD DIVERSITY AND CORPORATE RISK: EVIDENCE FROM INDONESIAN LISTED MANUFACTURING COMPANIES IN 2016-2019 - Fransisca Shania; Pamela Andriani; Tessa Vanina Soetanto (Institute of Research and Community Outreach - Petra Christian University, 2022)
Recently, board diversity has become an essential part of the modern business environment. Its awareness rises since it affects how the board carries out its duties, the board's efficacy, and the risk-taking behavior, leading to companies' outcomes and value. Therefore, the researchers conducted the study to know the impact of board diversity, precisely, the Board of Commissioner and corporate risk with the diversity of gender, age, nationality, education, and tenure. Board size, market to book ratio, tangibility, leverage, and profitability were used as control variables. This study focused on Indonesia's manufacturing companies listed in the IDX during 2016-2019, with 300 sample data collected from 75 companies. The data gathered were further analyzed using multiple linear regression. As a result, nationality diversity, tangibility, leverage, and profitability significantly affect corporate risk. Inversely, diversity of gender, age, education, tenure, the board size, and market-to-book ratio do not significantly affect corporate risk.